2015
DOI: 10.1186/s13034-015-0071-6
|View full text |Cite
|
Sign up to set email alerts
|

Research with adolescents who engage in non-suicidal self-injury: ethical considerations and challenges

Abstract: Non-suicidal self-injury (NSSI) has emerged as a significant psychiatric issue among youth. In addition to its high prevalence rates, NSSI is associated with a number of psychiatric issues and confers risk for varying degrees of physical injury. It is also a risk factor for attempted suicide. Thus, youth who engage in NSSI represent a vulnerable and high-risk population and researchers are likely to encounter a variety of ethical challenges when conducting NSSI research. Accordingly, it is critical that resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 50 publications
0
43
0
2
Order By: Relevance
“…Specifically, this includes having a basic understanding of NSSI, knowing how to broach the topic, being able to respond effectively when talking about NSSI with students, providing appropriate referral options, and engaging in self‐care, as well as being aware of recommended resources (see Appendix). The resources listed in the Appendix were selected on the basis of past research examining the quality of online NSSI material (Lewis et al, ) as well as literature highlighting and recommending several of these resources as a means to augment NSSI literacy and foster more effective responding to those who self‐injure (Hasking et al, ; Lewis, Heath, Michal, & Duggan, ; Lloyd‐Richardson, Lewis, Whitlock, Rodham, & Schatten, ). Dissemination of effective response guidelines should occur through materials provided at orientation, mental health service websites, and all relevant mental health or student wellness activities and events.…”
Section: Effective Responses To Nssi On College Campusesmentioning
confidence: 99%
“…Specifically, this includes having a basic understanding of NSSI, knowing how to broach the topic, being able to respond effectively when talking about NSSI with students, providing appropriate referral options, and engaging in self‐care, as well as being aware of recommended resources (see Appendix). The resources listed in the Appendix were selected on the basis of past research examining the quality of online NSSI material (Lewis et al, ) as well as literature highlighting and recommending several of these resources as a means to augment NSSI literacy and foster more effective responding to those who self‐injure (Hasking et al, ; Lewis, Heath, Michal, & Duggan, ; Lloyd‐Richardson, Lewis, Whitlock, Rodham, & Schatten, ). Dissemination of effective response guidelines should occur through materials provided at orientation, mental health service websites, and all relevant mental health or student wellness activities and events.…”
Section: Effective Responses To Nssi On College Campusesmentioning
confidence: 99%
“…Recent research has recommended taking steps to reduce any potential negative impact of study involvement on youth [ 21 ]. Mood elevation techniques have been employed following lab-based self-harm research [ 28 , 29 ] and studies using other methods [ 7 , 30 ] and are also recommended in online settings [ 24 , 31 ]. An additional aim of the present study was to evaluate the use of a simple mood elevation tool that can easily be incorporated into a paper-based survey.…”
Section: Introductionmentioning
confidence: 99%
“…Using this approach, the psychometric analyses revealed that the STOP-SReFS and the STOP-SRiFS were reliable and valid instruments for assessing suicidality risk and resilience factors in adolescents. The fact that the STOP-SRiFS and the STOP-SReFS are more age-specific scales, which have been designed and worded specifically for the adolescent population, and that they can be completed online, decreasing completion time and ensuring accessibility at all times, increases their potential applicability in an adolescent population [29]. As suicidal behaviour depends on diverse clinical, psychological, sociological, and biological factors, the consensus is that a multi-informant evaluation is strongly recommended [21].…”
Section: Discussionmentioning
confidence: 99%